2017
DOI: 10.1002/glia.23125
|View full text |Cite
|
Sign up to set email alerts
|

A sweet taste receptor‐dependent mechanism of glucosensing in hypothalamic tanycytes

Abstract: Hypothalamic tanycytes are glial‐like glucosensitive cells that contact the cerebrospinal fluid of the third ventricle, and send processes into the hypothalamic nuclei that control food intake and body weight. The mechanism of tanycyte glucosensing remains undetermined. While tanycytes express the components associated with the glucosensing of the pancreatic β cell, they respond to nonmetabolisable glucose analogues via an ATP receptor‐dependent mechanism. Here, we show that tanycytes in rodents respond to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 67 publications
2
85
0
1
Order By: Relevance
“…Previously, it has been shown that tanycytes respond rapidly (minor to 2 min) to glucose by generating calcium waves that in vitro we shown are partly dependent on the glucose transporter, GLUT2 and depending of glycolysis and not by oxidative phosphorylation, showing the these cells have a high glycolytic activity (Benford et al, 2017; Frayling, Britton, & Dale, 2011; Orellana et al, 2012). The signals that originate by increased glucose can mediate cellular responses that could control the activity of orexigenic and anorexigenic neurons.…”
Section: Discussionsupporting
confidence: 53%
“…Previously, it has been shown that tanycytes respond rapidly (minor to 2 min) to glucose by generating calcium waves that in vitro we shown are partly dependent on the glucose transporter, GLUT2 and depending of glycolysis and not by oxidative phosphorylation, showing the these cells have a high glycolytic activity (Benford et al, 2017; Frayling, Britton, & Dale, 2011; Orellana et al, 2012). The signals that originate by increased glucose can mediate cellular responses that could control the activity of orexigenic and anorexigenic neurons.…”
Section: Discussionsupporting
confidence: 53%
“…Tanycytes are a specialised type of ependymal cells, which line the walls of the 3V and send long processes toward hypothalamic nuclei and the ME/PT region (Figure ). The strategic location of tanycytes at the interface between the cerebrospinal fluid and the pituitary blood flow at the ME suggests key functions in the blood‐brain barrier and in the selective transport of molecules between compartments and in nutrient sensing . Even though these cells were described over a century ago, and their morphology has been studied extensively, comparatively little is known regarding their functions .…”
Section: Tanycytes: Different Subtypes and Different Roles?mentioning
confidence: 99%
“…The strategic location of tanycytes at the interface between the cerebrospinal fluid and the pituitary blood flow at the ME suggests key functions in the blood-brain barrier and in the selective transport of molecules between compartments 100,101 and in nutrient sensing. 102,103 Even though these cells were described over a century ago, and their morphology has been studied extensively, comparatively little is known regarding their functions. 101 Although this classification has been useful, recent data show that it largely undermines the diversity of tanycytes.…”
Section: Tanyc Y Te S: D Ifferent Subt Ype S and D Ifferent Role S?mentioning
confidence: 99%
“…These findings suggest that actually tanycytes and pancreatic β cells use very similar glucosensing mechanism. However, recent studies indicate that there is another glucosensing machinery in tanycytes based on sweet taste receptor which is a heterodimer consisting of Tas1r2 and Tas1r3 receptor subunits [24]. Their findings using Tas1r2 null mice suggest that the proportion of glucose-insensitive tanycytes is increased.…”
Section: Glucose Homeostasis By Tanycytesmentioning
confidence: 99%